(untitled) (Research, Society and Development, 2022)
Objective: To evaluate and classify the risk of falls in post-cesarean section women. Methods: a descriptive cross-sectional study was conducted in a public hospital in the Federal District, Brazil from October to December 2017 involving 222 women. Results: women were on average 29 years old (±6.1); 64.9% (n=144) had complete high school education; 42.7% (n=95) were housewives, 80% (n=177) had gestational age between 37 and 41 weeks. 42.3% (n=94) had a low risk for falls; in 57.6% (n=128), medium and high risk for falls were verified for most cases, being the first 30 hours post-section period with higher risk. The application of the Morse Scale to assess the risk of falls showed higher proportions between medium and high risk of falls. Conclusion: the importance of routinely assessing the risk of falls in the studied population was verified to institute measures that minimize the occurrence of this event. It is recommended to extend these findings to other services in Brazil and worldwide to prevent falls and promote safety in obstetric care for women after cesarean delivery, especially when they perform their first ambulation.